Fabrication of antiferroelectric NaNbO3-CaSnO3 film by pulsed laser deposition. (13th July 2021) - Beppu, Kosuke; Funatomi, Fumiya; Adachi, Hideaki; Wada, Takahiro
Abstract: In this study, we fabricated a 0.98NaNbO3 -0.02CaSnO3 film on SrRuO3 coated (001)SrTiO3 single crystal substrate by pulsed laser deposition. A tiny amount of CaSnO3 alloying into NaNbO3 stabilized the antiferroelectric phase of NaNbO3 . The c -axis of stabilized antiferroelectric phase in the 0.98NaNbO3 -0.02CaSnO3 film grew along two directions of the in-plane and out-of-plane directions. These two types of antiferroelectric domains contributed to the stabilization of the antiferroelectric phase under a large applied electric field. The 0.98NaNbO3 -0.02CaSnO3 film showed antiferroelectric double P–E response even at a high temperature of 180 °C and had energy storage property of recoverable energy storage density ( W r ) of 1.7 J cm −3 and storage efficiency ( η ) of 52%.